2016
DOI: 10.1089/can.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Medical Cannabis Users: Patterns of Use and Perceived Efficacy

Abstract: Background: The political climate around Cannabis as a medicine is rapidly changing. Legislators are adopting policies regarding appropriate medical applications, while the paucity of research may make policy decisions around conditions for which Cannabis is an effective medicine difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
210
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(245 citation statements)
references
References 52 publications
30
210
1
4
Order By: Relevance
“…In 2017, Lucas and Walsh19 found that 63% of 271 such subjects reported substituting cannabis for prescription drugs such as opioids (30%), benzodiazepines (16%) and antidepressants (12%), representing the same top three categories as data presented here. These findings also agree with our previous data showing that medical cannabis users report using cannabis most frequently to manage pain, anxiety and depression 6. The present study contributes to a greater understanding of substitution across specific classes of prescription drugs in a largely US-based sample, in a much larger cohort and cross-section, occurring among both medical and non-medical subjects, and in areas without legal access.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In 2017, Lucas and Walsh19 found that 63% of 271 such subjects reported substituting cannabis for prescription drugs such as opioids (30%), benzodiazepines (16%) and antidepressants (12%), representing the same top three categories as data presented here. These findings also agree with our previous data showing that medical cannabis users report using cannabis most frequently to manage pain, anxiety and depression 6. The present study contributes to a greater understanding of substitution across specific classes of prescription drugs in a largely US-based sample, in a much larger cohort and cross-section, occurring among both medical and non-medical subjects, and in areas without legal access.…”
Section: Discussionsupporting
confidence: 92%
“…The US Centers for Disease Control and Prevention (CDC) has issued federal guidelines on the long-term use of opiates, noting concerns that there may be negative unintended consequences associated with dose reduction, such as patients switching to the use of heroin 5. An alternative for patients with chronic pain is switching to the use of cannabis to navigate dose reduction and to treat their pain and/or comorbid conditions outright 6. A recent open-label, prospective study suggests that medical cannabis may decrease opioid use and benefit patients with treatment-resistant pain 7…”
Section: Introductionmentioning
confidence: 99%
“…As the survey was conducted immediately before Australian regulatory changes in November 2016, it is not surprising that almost all participants reported using illicit preparations. Like other international surveys, 10 12 we found that medical cannabis is used for a diverse range of health conditions, especially pain, mental health, sleep, and neurological conditions. More than 80% of respondents indicated that medical cannabis effectively managed their target symptom.…”
Section: Discussionsupporting
confidence: 70%
“…The survey questions were developed by the investigators, building upon previous consumer surveys [10][11][12][13] and incorporating questions relevant to current Australian conditions. Areas of enquiry included: participant characteristics; medical conditions and symptoms for which medical cannabis was used, in structured checklists of conditions and symptoms for which medical cannabis use has previously been reported; current and lifetime patterns of cannabis use, including preparation type and source, frequency (days in past month, average number times per day) and route of use, and cost; perceived benefits and harms associated with medical cannabis, including side effects (symptom checklist), social Abstract Objective: To explore patterns of cannabis use for medical purposes in Australia immediately prior to the 2016 legislation for frameworks for medical cannabis use.…”
Section: Methodsmentioning
confidence: 99%
“…In retrospective studies, a similar association between cannabis use and a reduction in opiate use for chronic pain has been observed . The use of cannabis as an alternative to pharmaceutical drugs for pain treatment has also been reported . The notion that the use of cannabis could result in a reduction of opioid use is supported by the fact that the opioid overdose mortality rates are reduced in states where medical cannabis has been legalized .…”
Section: What Considerations Should Pharmacy Practice Physicians Anmentioning
confidence: 67%